Configuration optimization of an enhanced ejector heat exchanger based on an ejector refrigerator and a plate heat exchanger. (1st December 2018) - Sun, Fangtian; Chen, Xu; Fu, Lin; Zhang, Shigang
Abstract: Ejector heat exchanger has good performance in heat transfer, but its regulating characteristics are poor, and to improve its regulating characteristics, an enhanced ejector heat exchanger (EHE) with a pressure booster is presented. According to the difference in location of the pressure booster, the enhanced ejector heat exchangers are divided into two types. One is EHE-MF with its pressure booster located in the pipeline between outlet of ejector and refrigerant inlet of the condenser. The other is EHE-SF with its pressure booster located in the pipeline between secondary fluid inlet of ejector and refrigerant outlet of the evaporator. The two enhanced ejector heat exchangers have been analyzed from the perspective of thermodynamics. The results show that the location of pressure booster in the pipeline between outlet of ejector and refrigerant inlet of the condenser contributes to decreasing boosted pressure and power and increasing product exergy efficiency. The EHE-MF has higher thermodynamic performance, and its system configuration is optimal from the perspective of thermodynamics. Highlights: Heat transfer effectiveness of EHE-MF is much higher than 1. Pressure booster can improve regulation performance of the ejector heat exchanger. Product exergy efficiency of EHE-MF is higher than that of EHE-SF. Power consumption of the pressure booster in EHE-MF is lower than that in EHE-SF. Configuration of EHE-MF is better than that of EHE-SF due to higher performance.